PREVALENSI LOW BACK PAIN PADA TERAPIS GIGI DAN MULUT DI PUSKESMAS WILAYAH KABUPATEN MAJALENGKA - Sapriliani Rahayu, Dian; Nurnaningsih, Hera; Chaerudin, Denden Ridwan; Herijulianti, Eliza (Jurnal Terapi Gigi dan Mulut, 2023)
The dental and oral therapist profession carries inherent risks to occupational health and safety, including musculoskeletal disorders like lower back pain (LBP). In Indonesia, LBP prevalence sits at 18%, and data from 2013 reveals that 11.9% of Indonesian healthcare workers suffer from musculoskeletal diseases. This study aimed to determine the prevalence of LBP among dental and oral therapists, both operators and assistants, at the Majalengka Regency Health Center. Using a descriptive approach and purposive sampling, the study enrolled 22 participants in April 2023. Data collection employed questionnaires and the Nordic Body Map (NBM), with analysis relying on the disease prevalence formula. The results yielded striking differences: 100% of operators (11 individuals) reported LBP, while only 72.7% of assistants (8 individuals) experienced the same. This disparity highlights the elevated risk faced by operators, suggesting a need for targeted interventions to address their occupational LBP burden. By streamlining the wording and focusing on key findings, this revised paragraph improves clarity and conciseness. It effectively conveys the study's purpose, methodology, and results, emphasizing the concerningly high LBP prevalence among dental and oral therapist operators.